Menentukan Kualitas Hasil Perbaikan Beton Bangunan Dermaga Dengan Metode Inspeksi Teknik - Sulardi Sulardi (Media Ilmiah Teknik Sipil, 2017)
The research objective was to provide an overview of the engineering inspection methods used in determine the quality of repair results and the quality of the results of concrete repair based on the results of concrete repair what has been done. The research method is carried out by engineering inspection methods which include visual tests and rebar test of concrete surface, compressive strength test with hammer test, test for concrete homogeneity with UPV test, test profometer concrete thickness blanket, cast drilled concrete core sampling, tensile test and concrete connection carbonation test of concrete surfaces with phenopthalein solution. The results of the research are chipping and grouting with specifications of microconcrete flowable material and repaired concrete surface protection with a thick mastic shield coating material specifications min. 300 micron DFT has been proven improve the strong quality of existing concrete by 69.40% from the compressive strength of the installed concrete design. Method Technical inspection, repair methods and specifications of the material used can be replicated for repairs damage and to determine the quality of similar repairs elsewhere.